9 The Statutes at Large of South Carolina: Containing the Acts Relating to Roads, Bridges and Ferries, With an Appendix, Containing the Militia Acts Prior to 1794, at 689-90 (David J. McCord ed., 1841) - (:unkn) unknown (My University, 1784)
"Excused from militia duty, except in times of alarm . . . all persons under the age of eighteen years or above the age of fifty years."
Keywords: MILITIAS